Effective knowledge transfer in virtual teams: linking contents and mechanisms. (30th November 2004) - Chai, Kah-Hin; Yap, Chee-Meng
This paper addresses the difficulties of knowledge transfer based on the characteristics of knowledge and suggests the possible transfer mechanisms virtual teams might use. Thus far, the discussion on knowledge transfer has tended to be identifying the drivers and inhibitors for effective transfer such as the ability to transfer and receive of the individuals involved, and the context in which the sharing takes place. One question that has received relative little attention – and that is central to effective knowledge transfer – is when to use what type of transfer mechanism. We propose that – all else being equal – the choice of mechanisms is determined by the tacitness and embeddedness of the knowledge to be transferred. Knowledge with high degree of tacitness should be transferred by rich media, while knowledge with high embeddedness should be transferred by media with high transfer capacity.